The control system for radiation sterilization of health-care products at the accelerator LU-10 - Boriskin, V.N.; Dovbnya, A.N.; Karasyov, S. P.; Nikiforov, V.I.; Pomatsalyuk, R.I.; Tenishev, A.Eh.; Uvarov, V.L.; Shevchenko, V.A.; Shlyakhov, I.N. (Вопросы атомной науки и техники, 2006)
The regulatory documents for the technological process of sterilization (DSTU ISO 11 137:2003 and others) set requirements on monitoring, maintaining and archiving the basic parameters of the process. To meet the requirements, an automated control system was created at the LU-10. It includes a PC-controlled beam scanner, technological measuring channels (TMC), and also a set of working standards to calibrate the channels. The CAMAC standard was used as an interface. The software of the complex provides the real-time processing of information on the beam parameters, their control, archiving, and also the information exchange within the local-area technological network. The presence of the Customer Database comprising the characteristics of incoming products makes it possible to optimize the process conditions for the products by the computer simulation method.